EFEKTIVITAS KINERJA BADAN PERMUSYAWARATAN RAKYAT NAGARI (BPRN) DALAM PENYELENGGARAAN PEMERINTAHAN NAGARI DI NAGARI TAPI SELO KABUPATEN TANAH DATAR - Devan Adius Faroqi; Hasbullah Malau (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2020)
This study describes the effectiveness of BPRN performance in the implementation of Nagari governance in Nagari Tapi Selo, Tanah Datar Regency. BPRN as the legislative body of Nagari Government in Nagari Tapi Selo, Tanah Datar Regency. BPRN has the duties and functions as legislation, receiving and conveying the aspirations of the village community, supervising the performance of the village guardian, and establishing the Nagari Budget (APBNagari) together with the Nagari guardian This research method, using descriptive qualitative, in determining informants using purposive sampling technique, testing the validity of the data using triangulation techniques, and data collection techniques using interviews, documentation study and focus group discussion (FGD). The results of this study indicate that the performance of BPRN Nagari Tapi Selo has not been effective because not all of its duties and functions are running well. BPRN's performance, when viewed from Mohammad Mahsun's theory, already has input although not all of it has been fulfilled, has carried out a performance process even though it is not fast enough to work, has outputs and outcomes, and has had the impact and benefit of its performance. Although the performance of BPRN still has obstacles to face